Trends in functional programming - Gilmore, Stephen (Trends in Functional Programming, 2005)
This book collects the latest research developments in the use of functional programming languages. The contents highlight major research goals and engineering concerns in the subject including: real-time and resource-bounded functional programming; connections between static analysis methods and functional programming; implementation of mobile code functional languages; automated testing of application programs and system models; These research contributions are drawn from the international symposium on Trends in Functional Programming. This meeting provides a vital forum for the dissemination of the latest technical advances in the field.